ASSOCIATION OF AGE AND INFORMATION HISTORY WITH ADOLESCENT GIRLS' KNOWLEDGE OF PRECONCEPTION HEALTH IN BANJARMASIN - Suryati Suryati; Maria Ulfa; Nadya Puteri (Jurnal Kebidanan Khatulistiwa, 2026)
Background: Preconception health needs to be introduced during adolescence because nutritional status, anemia prevention, reproductive health, mental health, and healthy lifestyle practices before pregnancy influence women's readiness for reproductive life. Previous studies on adolescent preconception health have mostly been descriptive, so analysis of related factors is needed. Purpose: This study aimed to analyze the association of age and history of receiving information with adolescent girls' knowledge of preconception health in Banjarmasin City. Methods: This analytical quantitative study used a cross-sectional approach. The sample consisted of 35 adolescent girls aged 19-21 years selected through accidental sampling. Data were collected in May 2026 using a Google Form questionnaire containing 20 true-false knowledge statements. Data were analyzed using univariate analysis and bivariate analysis with the Kruskal-Wallis and Mann-Whitney tests. Results: Most respondents were 19 years old (45.7%), almost all were college students (97.1%), and 51.4% had previously received preconception health information. Most respondents had good knowledge (91.4%). Bivariate analysis showed significant differences in knowledge scores by age (p=0.016) and history of receiving information (p=0.002). Conclusion: Adolescent girls' knowledge of preconception health was generally good. Age and information history were associated with knowledge scores, indicating the importance of equitable and continuous preconception education during adolescence